Phase I trial of gemcitabine and candesartan combination therapy in normotensive patients with advanced pancreatic cancer: GECA1 - Nakai, Yousuke (Cancer Sci, 2012)
Our retrospective study showed inhibition of the renin–angiotensin system was associated with better outcomes in patients with advanced pancreatic cancer receiving gemcitabine. The primary objective of this phase I study was to determine the recommended dose of candesartan in combination with gemcitabine in normotensive patients with advanced pancreatic cancer. Candesartan was given orally at an escalating dose (4, 8, 16, and 32 mg) q.d. daily, and gemcitabine was given 1000 mg/m(2) 30 min i.v. on days 1, 8, and 15, repeated every 4 weeks. Dose‐limiting toxicity (DLT) was defined as grade 4 hematological toxicities, grade 2 hypotension, abnormal creatinine or potassium, and grade 3 or 4 other non‐hematological toxicities. A standard “3+3” phase I dose‐escalation design was used. A total of 14 patients (candesartan 4 mg, three patients; 8 mg, three patients; 16 mg, six patients; 32 mg, two patients) were enrolled. One of six patients at 16 mg showed DLT of grade 4 neutropenia and two of two patients at 32 mg showed DLT of grade 2 hypotension. Response rate and disease control rate were 0% and 79%, respectively. Progression‐free survival and overall survival were 7.6 and 22.9 months, respectively. Candesartan 16 mg is the recommended dose in combination with gemcitabine in the treatment of advanced pancreatic cancer. (UMIN CTR: UMIN000002152) (Cancer Sci, doi: 10.1111/j.1349‐7006.2012.02311.x, 2012)